2018
DOI: 10.1111/jwas.12561
|View full text |Cite
|
Sign up to set email alerts
|

A novel micro‐organism for removing excess ammonia‐N in seawater ponds and the effect of Cobetia amphilecti on the growth and immune parameters of Litopenaeus vannamei

Abstract: To investigate the feasibility of using micro‐organisms for ammonia‐N removal, six strains were isolated from Chinese white shrimp, Fenneropenaeus chinensis, seawater culture ponds in Dongying (Shandong, China). Of these, strain DY‐01, which exhibited the highest capacity to degrade ammonia‐N, removed 61.7% of the total ammonia‐N (50 mg/L) in 8 hr. An investigation of the factors affecting the removal efficiency indicated the optimum conditions to be 30°C, pH 8.0, and a salinity level of 30 g/L; 16S rDNA gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…As for immune parameters, the total hemocyte count, phagocytic percent, and antibacterial activity were all enhanced, with no significant difference between the treatments and control group, according to Huang et al (2017) and Lv et al (2019). In this study, all immune parameters of L. vannamei showed significant differences in comparison with the control, which confirmed that AB15 and NB14 owned high ability to enhance immunity of L. vannamei .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…As for immune parameters, the total hemocyte count, phagocytic percent, and antibacterial activity were all enhanced, with no significant difference between the treatments and control group, according to Huang et al (2017) and Lv et al (2019). In this study, all immune parameters of L. vannamei showed significant differences in comparison with the control, which confirmed that AB15 and NB14 owned high ability to enhance immunity of L. vannamei .…”
Section: Discussionmentioning
confidence: 87%
“…Temperature and the initial pH usually make effects on the growth of microorganism and their absorption and utilization of substances via changing enzyme activity (Dong & Cai, 2001; Verstraete & Focht, 1977; Wang, Chang, Yu, Li, & Xu, 2007). Most of the reported NH 4 + ‐N and NO 2 − ‐N removal bacteria have optimum temperatures ranging from 25 to 40°C (Huang et al, 2017; Saleh‐Lakha et al, 2009; Qing et al, 2018) and the optimal pH is often at the scope of pH 7.0–9.0 (Huang et al, 2017; Lei, Jia, Chen, & Hu, 2019; Lv, Pan, Zhang, Li, & Zhang, 2019), which were paralleled with the results of strain AB15 at 25°C, pH 7.5, and strain NB14 at 30°C and pH 8.0 in this study. Beyond that, NaCl is essential to enzyme activities of the strain originated from the marine ecosystem (Duan, Fang, Su, Chen, & Lin, 2015), while cell plasmolysis and activity loss of microorganism caused by too high salinity may lead to the deteriorated ammonia removal efficiency (Uygur & Kargi, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, the genome assembly lengths of Cobetia amphilecti N-80, Cobetia amphilecti B2M13 and Cobetia amphilecti KMM296 are 4.16 Mb, 4.29 Mb, and 3.97 Mb, with 1, 27, and 97 scaffolds, respectively. Cobetia amphilecti N-80 is more studied than Halomonas profundus 13 and has been shown to possess ammonia-N degrading [59], a novel glutaminase-free L-asparaginase [60], antibiofilm activity and biopreservative effects on meat products [61], bacteriocinogenic potential [62] and so on. This may be due to the wider distribution of Cobetia amphilecti N-80, which is found in seawater culture ponds [59], mangrove sediments [60], ready-to-cook meats [61], ecosystems within the Sea of Japan [62] and elsewhere.…”
Section: Comparison Of the Two Strainsmentioning
confidence: 99%
“…Cobetia amphilecti N-80 is more studied than Halomonas profundus 13 and has been shown to possess ammonia-N degrading [59], a novel glutaminase-free L-asparaginase [60], antibiofilm activity and biopreservative effects on meat products [61], bacteriocinogenic potential [62] and so on. This may be due to the wider distribution of Cobetia amphilecti N-80, which is found in seawater culture ponds [59], mangrove sediments [60], ready-to-cook meats [61], ecosystems within the Sea of Japan [62] and elsewhere. However, there are no detailed reports on its nitrification and denitrification abilities.…”
Section: Comparison Of the Two Strainsmentioning
confidence: 99%
See 1 more Smart Citation